Carl Schmitt on historic mentality and essence of Weimar constitution - Шумський, Л. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article reveals the relevance of retaining and enforcement of effectiveness of the state’s principal law in terms of C. Shmitt's conception and philosophic principles through the following structural peculiarities of Weimar constitution: federalism, parliamentarism, democracy. Special attention is given to the forth element – the rule-of-law state, which due to its bourgeois ideological content, fails to reveal its historic functions one of which is integration of proletariat into political community.